2014
DOI: 10.1155/2014/313575
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Anatomical Position of Vermiform Appendix among Iranian Population: An Old Issue Which Has Not Lost Its Importance

Abstract: Vermiform appendix has diverse anatomical positions, lengths, and conditions of mesoappendix. Knowing the exact anatomical position of vermiform appendix is important in view of surgeons for on-time diagnosis and management of acute appendicitis. The aim of present study is determination of these characteristics of vermiform appendix among Iranian population. The present study was conducted on 200 bodies, selected from the dead bodies that had been referred to local bureau of legal medicine, Zenjan province, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
3
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 9 publications
4
39
3
10
Order By: Relevance
“…They also reported that individuals with older age have a longer length of the appendix similar to the findings of present study. [13] Contrary to our finding one study in Bangladesh on 56 males reported no significant negative correlation between age of the subject and length of the appendix [15] , while another study in Bangladesh on 60 postmortem cases showed a highly significant negative correlation between age of the subject and length of appendix. [16] The cause of such gradual increment in appendix length with age in this study might be accounted to dietary habits and racial difference.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…They also reported that individuals with older age have a longer length of the appendix similar to the findings of present study. [13] Contrary to our finding one study in Bangladesh on 56 males reported no significant negative correlation between age of the subject and length of the appendix [15] , while another study in Bangladesh on 60 postmortem cases showed a highly significant negative correlation between age of the subject and length of appendix. [16] The cause of such gradual increment in appendix length with age in this study might be accounted to dietary habits and racial difference.…”
Section: Discussioncontrasting
confidence: 99%
“…[12] They proposed that after an initial growth period during early infancy up to about 3 years, the appendix achieves its adult proportions and does not continue to grow throughout childhood. [12] In some other studies on 200 bodies from Iranian population [13] and 60 cadavers of the Sudanese population [14] , they found a significant association between the appendix length and different age groups. They also reported that individuals with older age have a longer length of the appendix similar to the findings of present study.…”
Section: Discussionmentioning
confidence: 89%
“…After the completion of the gut rotation, the caecal diverticulum occupies a position on the right side of the abdominal cavity [9]. In our study, mean age of individual was 38.7 years which comparable with the similar study done by Ghorbani A et al [12]. In present study, the most common position of appendix was retrocaecaland the lowest was subhepatic position.…”
Section: Discussionsupporting
confidence: 88%
“…The average length of appendix was 6.61 cm in males and 6.06 cm in females in Gorgan [10]. Tofighi in Tehran [24] and Ghorbani et al [9] in Zanjan have reported that the mean length of appendix was 9.12 cm in males and 8.03 cm in females. In addition, significant correlation was found between appendix weight and age, which was consistent with our finding [11].…”
Section: Discussionmentioning
confidence: 99%
“…The mean length of appendix was reported 6.03 cm in Thailand [5]. This value obtained for weight ranges from 6.33 cm to 8.57 cm in Iranian population [9,10,24]. The common position of the appendix was retrocaecal in India [3,15,22,25], retroileal in Thailand and pelvic in Iran [9,10,24].…”
Section: Introductionmentioning
confidence: 99%